Digital Marketing Strategies for Service Quality in a Primary Care Health Clinic (LACCEI, 2024)
The research summarizes the study of [1]. The objective was to design a digital marketing model to improve the quality of service of the company "Servicios Médicos ElyLab" against Covid-19. The research was applied, using a cross-sectional, non-experimental, descriptive-explanatory design. A questionnaire validated by expert judgment (α-Cronbach's 0.905) was administered to 40 clients. The 4 phases of the Sainz methodology were carried out as follows: Phase I involved analyzing and evaluating the organization's situation, including the formulation of its mission and vision, external analysis (MEFE), competitive analysis (Porter's 5 Forces), and internal analysis (MEFI). Phase II involved establishing marketing objectives, Phase III involved selecting marketing tactics, including the identification and selection of strategies, and in Phase IV, the formulation of execution plans and the development of a balanced control panel. The economic evaluation showed positive results (VAN S/.63046, IRR of 44% and B/C of S/. 1.90).